QUESTIONING THE UTILITY OF 'CULTURAL COMPETENCY' IN CARING FOR OLDER CHINESE PATIENTS AT THE END-OF-LIFE. (11th November 2018) - Mirza, R; Klinger, C
Abstract: With increasing cultural diversity in North America, ensuring that healthcare professionals are able to provide appropriate care to individuals from a wide range of cultural backgrounds, commonly described as "cultural competency", has become a priority issue within the healthcare system. More specifically, culturally competent end-of-life care is essential for clinicians to prioritize as the individualized needs of older patients and their families, regardless of cultural background or ethnicity, are unique and context driven. The aim of this study was to explore the usefulness of "cultural competency" as a way to improve the ability of healthcare practitioners to meet the healthcare needs of elderly Chinese patients at the end-of-life in Canada. Using a qualitative research design, 49 in-depth interviews with 23 participants were conducted. Our results are organized into six vignettes, which illustrate how "Chinese culture" is not a commonly understood or experienced phenomenon, but that the individual ways in which "culture" is interpreted by patients and healthcare providers around issues of death and dying. Furthermore, the results from this study challenge the assumption that all members of an ethnic or cultural group share similar views on end-of-life and palliative care. Finally, how and why cultural explanations are used to justify health care-related requests and decisions, at the end-of life are explored. Not all "Chinese patients" had the same "cultural" needs or sensitivities and underscore the need for good communication with patients and their family members to facilitate healthcare providers' understanding of patients' needs and values regardless of their ethnic background.